2010
DOI: 10.3945/ajcn.2009.28925
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns associated with fat and bone mass in young children

Abstract: Beginning at preschool age, diets rich in dark-green and deep-yellow vegetables and low in fried foods may lead to healthy fat and bone mass accrual in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 27 publications
7
103
1
3
Order By: Relevance
“…The 12-week gardening, nutrition and cooking programme called LA Sprouts, which was taught during an after-school programme to low-income, primarily Hispanic, 3rd-5th grade students, found that the garden programme resulted in reductions in BMI, waist circumference and blood pressure. While substantial research has been conducted to show that healthy diets, specifically diets high in F&V, are linked to reductions in obesity and obesity-related diseases such as type 2 diabetes and cardiovascular risk factors (40,41) , more studies examining the direct impact of a garden-based programme on obesity and related diseases are warranted. Considering Ozer's evaluation framework in 2007 (11) , there are multiple pathways by which school garden programmes may potentially strengthen the healthy development of students, including dietary intake, academic achievement/engagement and a sense of connection to schools, while enhancing the relationship of the school to the family and broader community.…”
Section: Discussionmentioning
confidence: 99%
“…The 12-week gardening, nutrition and cooking programme called LA Sprouts, which was taught during an after-school programme to low-income, primarily Hispanic, 3rd-5th grade students, found that the garden programme resulted in reductions in BMI, waist circumference and blood pressure. While substantial research has been conducted to show that healthy diets, specifically diets high in F&V, are linked to reductions in obesity and obesity-related diseases such as type 2 diabetes and cardiovascular risk factors (40,41) , more studies examining the direct impact of a garden-based programme on obesity and related diseases are warranted. Considering Ozer's evaluation framework in 2007 (11) , there are multiple pathways by which school garden programmes may potentially strengthen the healthy development of students, including dietary intake, academic achievement/engagement and a sense of connection to schools, while enhancing the relationship of the school to the family and broader community.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also measured BMD at the trochanter (22,36,37,49), Ward's area (22,36,49), total hip (15,16,39), distal radius (13,39,41,60), radius shaft (18,36,39), total femur (24,37), calcaneus (43,47), intertrochanteric area (49), distal ulna (13), whole arm, whole leg and whole pelvis (23), distal and ultradistal forearm (45), and distal tibia and tibia shaft (38). Bone mineral content (BMC) also was measured in some studies (n = 7) (13,14,16,19,(42)(43)(44).…”
Section: Bone Outcome Measurementsmentioning
confidence: 99%
“…Two studies used bone and body composition variables (42,43), and 1 study used bone-related nutrient intake as intermediate response variables (44). Two dietary patterns were derived with the use of total body BMC and fat mass as response variables in children aged 4-8 y.…”
Section: Data-driven Dietary Patternsmentioning
confidence: 99%
“…Dietary patterns can summarize the combined and potentially synergistic effects of a repertoire of foods contributing to usual dietary intake in a defined population. Several nutritional epidemiology researchers have investigated the link between eating patterns and excess weight and have found a positive correlation between inadequate eating patterns and higher body mass index gain in children and adolescents 14,15,16,17 . However, this relationship was not observed in other studies 18,19,20 .…”
Section: Introductionmentioning
confidence: 99%